2022
DOI: 10.1055/s-0042-1758842
|View full text |Cite
|
Sign up to set email alerts
|

Craniotomy or Craniectomy for Acute Subdural Hematoma? Difference in Patient Characteristics and Outcomes at a Tertiary Care Hospital

Abstract: Objective This article compares the outcomes of patients with traumatic acute subdural hemorrhage (SDH) managed either with craniotomy (CO) or with decompressive craniectomy (DC). Methods In this single-center, retrospective analysis we included all adult patients with acute traumatic SDH who were treated either using CO or DC. Sixteen-year hospital data was reviewed for patient demographics, injury details, and hospital course. Outcomes were noted in terms of intraoperative blood loss, intensive car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Consequently, they were assessed for eligibility and full-text screening, which led to the inclusion of 17 studies. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 The searching and screening process is shown in the flowchart ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they were assessed for eligibility and full-text screening, which led to the inclusion of 17 studies. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 The searching and screening process is shown in the flowchart ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…More data is needed to standardize care since the situations that fall in between the two extremes are those in which surgeons retain discretion over the procedure they choose. 6 Therefore a systematic review and meta-analysis was performed to address the relative outcomes and complications of craniotomy when compared to decompressive craniectomy for acute SDH.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). 2 7 16 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 In the 42 articles within the quantitative analysis, 34 articles included patients operated on for ASDH, 2 16 24 25 26 27 30 31 33 34 35 37 38 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 …”
Section: Resultsmentioning
confidence: 99%
“…Nine point eight percent (4/41) of the studies, accounting for 945 patients, reported differences in baseline characteristics, brain CT features, and outcomes between patients who underwent craniotomy or DC. 40 48 50 61 Compared to patients who underwent craniotomy, patients who underwent DC were more likely to be younger (significant n = 734, p = 0.015; nonsignificant p = 46), to suffer from extra-cerebral-associated trauma lesions (significant n = 91, p = 0.001), to have a lower admission GCS score (significant n = 780, p = 0.034), and to present abnormal pupil examination (significant n = 46, p = 0.004). Patients who underwent DC were more likely to harbor serious brain CT scan features, such as important ASDH thickness (significant n = 808, p = 0.031), important midline shift (significant n = 808, p = 0.01), traumatic subarachnoid hemorrhage (significant n = 46, p = 0.003), and loss of basal cisterns (significant n = 256, p = 0.02).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation